Evidence of Immunosuppressive and Th2 Immune Polarizing Effects of Antidiabetic Momordica charantia Fruit Juice - Fachinan, Rufine; Fagninou, Adnette; Nekoua, P Magloire; Amoussa, A Madjid; ADJAGBA, Marius; LAGNIKA, LATIFOU; LALEYE, OLABISSI ANATOLE A.; MOUTAIROU, KABIROU; YESSOUFOU, AKADIRI (My University, 2017)
The mechanism of action of the antidiabetic capacity of Momordica charantia is still under investigation. Here, we assessed phytochemical compositions, antioxidant activity, and effects of total and filtered fruit and leafy stem juices of Momordica charantia on human T cell proliferation and differentiation through quantification of Th1/Th2 cytokines. In the absence of stimulation, total fruit and leafy stem juices induced significant T cell proliferation. Under PHA stimulation, both juices potentiated plant-induced T cell proliferation. However, the filtered fruit and leafy stem juices significantly inhibited PHA-stimulated T cell proliferation, while neither juice influenced T cell proliferation. Moreover, total and filtered fruit juice increased IL-4 secretion, while total and filtered leafy stem juice enhanced IFN-γ production. Phytochemical screening revealed the presence of tannins, flavonoids, anthocyans, steroids, and triterpenoids in both juices. Alkaloids, quinone derivatives, cardenolides, and cyanogenic derivatives were undetectable. The saponins present in total juices were undetectable after filtration. Moreover, both juices had appreciable antioxidant capacity. Our study supports the type 1 antidiabetic effect of filtered fruit juice of M. charantia which may be related to its immunosuppressive and T-helper 2 cell inducing capacities. Due to their immune-stimulatory activities and their ability to increase T-helper 1 cell cytokines, total fruit and leafy stem juices may serve in the treatment of immunodeficiency and certain infections.
Keywords: Momordica charantia; Diabetes; T-cell proliferation; Th1/Th2 cytokines